2020
DOI: 10.1089/scd.2019.0147
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Niche Conversion Strategy Induces Migration and Functional Neuronal Differentiation of Neural Precursor Cells Following Brain Injury

Abstract: Glial scars formed after brain injuries provide permissive cues for endogenous neural precursor/stem cells (eNP/ SCs) to undergo astrogenesis rather than neurogenesis. Following brain injury, eNP/SCs from the subventricular zone leave their niche, migrate to the injured cortex, and differentiate into reactive astrocytes that contribute to glial scar formation. In vivo neuronal reprogramming, directly converting non-neuronal cells such as reactive astrocytes or NG2 glia into neurons, has greatly improved brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Studies have found that mesenchymal stem‐cell transplantation can repair neuronal injury by regulating CXCL12/CXCR4 signaling with the beneficial effects mainly achieved through the replacement of injured cells (Chau et al, 2018; Hu et al., 2019), immunomodulation (Chen et al., 2018), and neurotrophic actions (Abati, Bresolin, Comi, & Corti, 2019). However, exogenously transplanted stem cells have low survival rates possibly due to immune rejection, acute inflammation, and lack of neurotrophic signals (Wang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that mesenchymal stem‐cell transplantation can repair neuronal injury by regulating CXCL12/CXCR4 signaling with the beneficial effects mainly achieved through the replacement of injured cells (Chau et al, 2018; Hu et al., 2019), immunomodulation (Chen et al., 2018), and neurotrophic actions (Abati, Bresolin, Comi, & Corti, 2019). However, exogenously transplanted stem cells have low survival rates possibly due to immune rejection, acute inflammation, and lack of neurotrophic signals (Wang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, exogenously transplanted stem cells have low survival rates possibly due to immune rejection, acute inflammation, and lack of neurotrophic signals (Wang et al, 2019).…”
mentioning
confidence: 99%
“…Under normal physiological conditions, the SVZ can generate mature astrocytes (Sohn et al, 2015) and following injury, the number of astrocytes produced by the SVZ drastically increases. Lineage tracing with the Nestin-CreER T2 promoter has been used to directly identify SVZ-derived progenitors migrating to the injury site, with the Nestin-CreER T2 :R26R-YFP/RFP traced cells predominately expressing the astrocytic marker GFAP within the injured striatal parenchyma after middle cerebral artery occlusion (MCAO) (Li et al, 2010), in the cortex after injury (PBS filling brain cavity) (Wang et al, 2019), cortical stroke (Benner et al, 2013;Faiz et al, 2015) or stab-wound injury (Burns et al, 2009). These studies reveal that the SVZ produces a more predominant astrocytic component than previously appreciated.…”
Section: Subventricular Zone-derived Astrocytes Response To Injurymentioning
confidence: 99%
“…Neural precursor cells (NPCs) in the SVZ of rodents can differentiate into neuroblasts and migrate through a pathway of aligned astrocytes known as the rostral migratory stream (RMS) to the olfactory bulb (OB), where they mature into functional granule, periglomerular, or glutamatergic interneurons and integrate into existing circuitry [3][4][5][6]. Following brain injury, SVZ neurogenesis is upregulated [7][8][9] and neuroblasts can divert from the SVZ-RMS-OB pathway, migrate toward injured brain regions, and mature into functional, phenotypically relevant neurons [10][11][12]. Further, experimentally enhancing the redirection of neuroblasts from the SVZ into injured regions can induce functional recovery following injury [10,[12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Following brain injury, SVZ neurogenesis is upregulated [7][8][9] and neuroblasts can divert from the SVZ-RMS-OB pathway, migrate toward injured brain regions, and mature into functional, phenotypically relevant neurons [10][11][12]. Further, experimentally enhancing the redirection of neuroblasts from the SVZ into injured regions can induce functional recovery following injury [10,[12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%